Identification of Maize (Zea mays L.) Germplasms for Resistant Sources against Turcicum Leaf Blight Disease - Bhaskar, A. Vijaya; Usharani, G.; Sravani, D. (International Journal of Bio-resource and Stress Management, 2022)
Maize ( The present studies were aimed to evaluate 302 maize entries for resistance against tturcicum leaf blight (TLB) disease in randomized blockdesign using a check at Agricultural Research Station, Karimnagar, Telangana State, India during rabi (November-2019-Febrauary-2020 and kharif (July- 2020-October-2020). During rabi- 2019−2020, out of 205 lines, 5 promising entries viz., IB-140, DHM-121, 17×605-1-2, 107×BML-7 and 186×BML-32 were identified with disease score 1 (resistant), 27 lines were recorded as moderately resistant, 2 lines were recorded as moderately susceptible and CM-202 entry was recorded 74.30% diseased leaf area (% DLA). During kharif-2020, out of 98 lines, 41 lines viz., 70531×CML156, 70530×BML45, 70530×11-2-1, 70425×BML6, 72554×50-2-1, 72555×BML7, 72343×50-2-1, 72336×11-2-1, 72336×CML156, 72343×BML45, 72603×66-1-1, 72513×CML156, 72343×66-1-1, 70531×BML45, 722603×CML-156, 72555×66-1-1, 72336×BML6, 70439×CML156, 70576×50-2-1, 72555×605-1-1, 72555×BML6, 72336×50-2-1, 72374×BML7, 72555×CML156, 72555×33-1-4, 70425×BML45, 72520×CML156, 72504×CML156, 70474×50-2-1, 72568×BML-14, 72686×PFSR3, 72260×CML156, 66-1-1, 524-3-2, 31-2-4, 207-1-3, 244-1-2, 540-2-3, 388-2-1, KML225 and 186-4-3 were identified as resistant lines to turcicum leaf blight disease (score 1), three lines were moderately resistant, 1 line CM-202 was noticed with high 72.46% diseased leaf area and severely affected by turcicum leaf blight and rated as susceptible during kharif, 2020.